2011
DOI: 10.1158/1078-0432.ccr-10-2467
|View full text |Cite
|
Sign up to set email alerts
|

Yes-Associated Protein 1 Exhibits Oncogenic Property in Gastric Cancer and Its Nuclear Accumulation Associates with Poor Prognosis

Abstract: Purpose: Yes-associated protein 1 (YAP1) is a multifunctional protein that can interact with different transcription factors to activate gene expression. The role of YAP1 in tumorigenesis is unclear. We aimed to investigate the functional role of YAP1 in tumorigenesis of gastric cancer.Experimental Design: YAP1 expresson in gastric adenocarcinoma was evaluated. The biological function was determined by proliferation assay, colony formation, cell invasion, and flow cytometric analysis through knocking down or e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
218
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(232 citation statements)
references
References 29 publications
11
218
1
2
Order By: Relevance
“…Another interesting biochemical observation was the activation of ERK in our Mob1-deficient keratinocytes: no connection between MOB1 and ERK has been reported to date. With respect to Hippo signaling, ERK can be activated by YAP1 (49) or suppressed by NF2 (50) or MST2 (51). Since NF2 and phospho-MST1/2 were not decreased in our Mob1-deficient keratinocytes (data not shown), we speculate that the increased YAP1 in these cells may have triggered their abnormal ERK activation.…”
Section: Discussionmentioning
confidence: 84%
“…Another interesting biochemical observation was the activation of ERK in our Mob1-deficient keratinocytes: no connection between MOB1 and ERK has been reported to date. With respect to Hippo signaling, ERK can be activated by YAP1 (49) or suppressed by NF2 (50) or MST2 (51). Since NF2 and phospho-MST1/2 were not decreased in our Mob1-deficient keratinocytes (data not shown), we speculate that the increased YAP1 in these cells may have triggered their abnormal ERK activation.…”
Section: Discussionmentioning
confidence: 84%
“…Hence, the apoptotic response to siRRM2 appeared to be cell context-dependent. It is uncertain whether the different TP53 status might contribute to the different apoptotic responses as MKN1 and MKN28 cells harbor the TP53 mutation, whereas AGS cells carry the wild type TP53 (17). It has been reported that antisense RRM2 downregulated RRM2 expression and sensitized a prostate cancer cell line PC3 to UV radiation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed as previously described (17). RRM2 protein was detected with a polyclonal anti-RRM2 antibody (Santa Cruz, 10846, 1:500).…”
Section: Cell Lines and Clinical Gastric Adenocarcinoma Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAPK pathway is known to be activated in a broad spectrum of human tumors, including human colorectal (25) and gastric cancer (26) and melanoma (27). We observed that activation of the MEK/ERK pathway was relatively weak in breast cancer cells, yet TM induced constitutive activation of the pathway as evidenced by increased phosphorylation (activation) form of ERK1/2 (P-ERK1/2).…”
Section: Discussionmentioning
confidence: 98%